Control of bubble ζ-potentials to improve the kinetics of bubble-particle interactions. (1st June 2020) - Huang, Kaiwu; Yoon, Roe-Hoan
Highlights: Force measurement in flotation films becomes more accurate at a slower approach speed. Control of bubble zeta-potential improves the kinetics of bubble-particle interaction. Attractive EDL force helps increase negative disjoining pressure and hence flotation kinetics. Abstract: Derjaguin and Dukhin (1961) developed a kinetic model for the bubble-particle interactions in flotation using the classical DLVO theory. According to the model, the energy barrier ( E 1 ) to flotation should increase with the square of particle ζ-potential due to the increase in the repulsive electrical double-layer (EDL) forces in the thin liquid films (TLFs) of water confined between the two dissimilar surfaces. In the present work, surface force measurements have been conducted by monitoring the changes in local curvatures of the air bubbles approaching flat silica surfaces of varying contact angles, while controlling the bubble ζ-potentials in alkyltrimethylammonium chloride (Cn TACl) solutions of varying chain lengths and concentrations. The results show that the kinetics of film thinning and contact angle formation increased with decreasing energy barriers. It has been found, however, that E 1  = 0 is not the sufficient condition for maximum kinetics, as the bubble-particle interaction continued to improve with further increases in the negative disjoining pressure in the TLFs. These findings can be attributed to the increase in the hydrodynamic forces in TLFs due to the increases in the attractive EDL and hydrophobic forces. The fundamental information obtained in the present work may be useful for developing novel flotation reagents and designing more efficient flotation machines.